Synthesis of a New Three-Dimensional Network Co-polymer and Studying the Ability of Drug Delivery System - Zahraa Mushtaq Abd Al-Aama (Journal of Global Pharma Technology, 2018)
In this work, a new co- polymer was synthesized from the reaction of pentarythritol with fumaric acid to form the linear co- polymer. Three different moles of acrylic acid monomer (0.5, 1.0 and 1.5 mole), were added to obtain three new co- polymers. Swelling of the polymer samples were measured in the buffer solution in the basic and acidic medium. The albumin protein was loaded onto the co- polymer samples and then the release of the albumin protein was measured in the acid and basic medium. The results obtained showed that the protein loading and release process in the basic medium were higher than in the acidic medium, indicating that the combined co-polymer is selective in the medium.Keywords: Hydro gel; Polymer; Condensation polymerization; Three-dimensional network; Selectivity; Swelling; Buffer solution; Drag delivery system.